2020
DOI: 10.6065/apem.2040002.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different criteria for the definition of insulin resistance and its relationship to metabolic risk in children and adolescents

Abstract: Childhood obesity frequently persists into adulthood, and is associated with insulin resistance (IR) and increased long-term morbidity and mortality. We compared IR criteria concerning 'age-specific cutoff points (ACOP)' and 'fixed cutoff points (FCOP)' for the identification of IR, and we investigated their correlation with metabolic syndrome (MS) Methods: The data were acquired from the 5 th Korea National Health and Nutrition Examination Survey (2010-2011). Participants aged from 10 to17 years underwent fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 39 publications
(73 reference statements)
3
19
0
Order By: Relevance
“…A previous study evaluated the frequencies of dyslipidemia and hyperglycemia in children with IR assessed by cutoff points of HOMA-IR; the frequencies of increased TC, LDL-C and TG, decreased HDL-C were all above 50% ( 35 ). Another study demonstrated that in a sample of Korean children and adolescents, metabolic syndrome increased 18.4-fold and each MetS component (including central obesity, hypertriglyceridemia, hypertension, low HDL-C, and hyperglycemia) increased 2.12–7.42-fold among participants with IR ( 40 ). However, they used different cutoff values of HOMA-IR for the diagnosis of IR.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study evaluated the frequencies of dyslipidemia and hyperglycemia in children with IR assessed by cutoff points of HOMA-IR; the frequencies of increased TC, LDL-C and TG, decreased HDL-C were all above 50% ( 35 ). Another study demonstrated that in a sample of Korean children and adolescents, metabolic syndrome increased 18.4-fold and each MetS component (including central obesity, hypertriglyceridemia, hypertension, low HDL-C, and hyperglycemia) increased 2.12–7.42-fold among participants with IR ( 40 ). However, they used different cutoff values of HOMA-IR for the diagnosis of IR.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of dyslipidemia in obese Korean adolescents is high and has been reported as 56.1%, and the 2017 clinical practice guidelines for dyslipidemia of Korean children and adolescents have been published [ 29 , 31 ]. Limited studies are available to define the risks of obesity-related comorbidities in Korean children and more studies are needed [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…I read Lee et al's recent article in the Annals of Pediatric Endocrinology & Metabolism with great interest [ 1 ]. The authors demonstrated that the determination of insulin resistance (IR) through age-corrected cutoff points correlates more strongly with metabolic syndrome (MS) than the use of fixed cutoff points.…”
mentioning
confidence: 99%
“…Despite IR being the main etiology of MS, the most widely accepted and used definition of MS from the International Diabetes Federation [ 5 ] does not use criteria for defining IR, but only places fasting glycemia as one of its diagnostic criteria. The article by Lee et al [ 1 ], as well as several others that have been published in recent years, clearly demonstrates that a suitable diagnosis of MS in adolescence needs to take into account IR. Several studies have demonstrated that fasting insulin or HOMA are appropriate indicators for this purpose.…”
mentioning
confidence: 99%
See 1 more Smart Citation